Khalwat Marriage Adat and Practices in Aceh: A Study on Adat Sanctions and Settlement Process of Khalwat Case - Rizki, Wahyu Fahrul (UIN Sunan Kalijaga, 2020)
Abstract: The study analyzes one of the traditions still underway in Aceh province, khalwat marriage. A khalwat marriage is a form of forced marriage as for khalwat offenders (those who are dating in a secluded place). The khalwat marriage itself is known to lead to some negative effects because many khalwat marriage couples were underage. Moreover, khalwat marriages arevalso not officially registered, and many couples decide to divorce soon after the wedding takes place. The paper attempts to investigate the reasons why adat law is still upheld vigorously in Aceh and why marriage is aplied as a adat sanction for khalwat offenders. To analyze and answer these questions, the researcher studied some essential works related to the application of adat law in Aceh and conducted some field observations and interview with some key informants. Using the sociological-anthropological approach, this research made the following conclusions: first, there has been a strict adat law enforcement in Aceh given the juridical support, sociological, and philosophical foundations. Second, some arguments to support the enforcement of forced marriage as adat sanction for khalwat offenders are: (1) the sanction is a form of tradition applied for a long time, (2) the sanction is applied as a way to preserve women’s marwah or dignity and her family, (3) the sanction is applied to uphold religious orders and this is the most fundamental sanction applied for khalwat offenders, and (4) the sanction serves as the extension of Qanun (Aceh Sharia Law) which applies only in certain regions.Abstrak: Tulisan ini mengkaji salah satu tradisi yang hingga kini masih terus berlangsung di Aceh, yakni pernikahan Khalwat. Pernikahan Khalwat merupakan bentuk sanksi adat bagi pelaku tindakan khalwat. Pernikahan khalwat itu sendiri memiliki sejumlah sisi negaif karena banyak di antara pasangan pernikahan Khalwat tersebut masih berada di bawah umur. Selain itu, pernikahan Khalwat juga sering tidak dicatatkan dan bahwa tidak sedikit dari pasangan pernikahan Khalwat yang memutuskan untuk bercerai tidak lama setelah proses pernikahan dilangsungkan. Tulisan ini berupaya menyelidiki penyebab mengapa hukum adat ini masih begitu kuat diberlakukan di Aceh dan mengapa pernikahan dijadikan sebagai sanksi bagi pelaku khalwat. Untuk mengkaji, menganalisis dan menjawab pertanyaan tersebut, peneliti telah menelaah sejumlah karya penting terkait pemberlakuan hukum adat di Aceh dan juga terjun langsung ke lapangan guna melakukan observasi dan mewawancarai sejumlah informan kunci. Dengan menggunakan pendekatan sosiologi-antropologi, diperolehlah kesimpulan: pertama, kuatnya hukum adat di Aceh karena ia didukung dan memiliki dasar yuridis, sosiologis, dan juga filosofis. Kedua, ada sejumlah argumen yang mendasari dijadikannya pernikahan sebagai sanksi Khalwat: (1) pemberian sanksi tersebut merupakan suatu tradisi yang telah diberlakukan sejak lama di Aceh; (2) untuk menjaga marwah atau kehormatan perempuan dan keluarganya, (3) menjalankan perintah agama dan ini merupakan faktor paling mendasar atas berlakunya sanksi Khalwat, dan (4) sebagai perpanjangan pelaksanaan Qanun Aceh yang keberlakuannya masih terbatas hanya pada wilayah tertentu saja.